EFFECTS OF TABLE TENNIS ON STRESS MANAGEMENT AND PSYCHOLOGICAL RESILIENCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In the modern world, a fast-paced lifestyle along with social and economic pressures has led to a significant increase in the level of stress experienced by individuals. Stress, in turn, can have serious negative effects not only on physical health but also on mental well-being and psychological stability. It has been scientifically proven that chronic stress may lead to conditions such as depression, anxiety, sleep disorders, and decreased cognitive abilities. Therefore, the search for effective methods of stress management and the strengthening of psychological resilience has become an urgent scientific and practical issue.